Manual Wheelchair Equipped with a Planetary Gear-Research Methodology and Preliminary Results - Mateusz Kukla; Bartosz Wieczorek; Łukasz Warguła; Dominik Rybarczyk; Jan Górecki (Applied Sciences, 2022)
The purpose of the study was to create a research methodology for testing the newly developed wheelchair drive, which allows the operator to choose the gear ratio and, thus, makes it possible to change the propulsion torque value. The aim was to choose such conditions in the experiment, that would result in great enough changes in the participant’s muscle load and body kinematics for it to be possible to register them with applied measuring methods. Surface electromyography was used to assess the effort that was required for the propulsion of a wheelchair under different conditions. Additionally, upper limb motion capture measurements were also performed. The preliminary results show that the muscular effort of the participant propelling the wheelchair increases with the load—resulting from both the gear ratio and the inclination angle. At the same time, the position of the motion range of upper limb individual segments changes significantly. Simultaneously, the mean value of the shoulder displacement and its angle of rotation decreases.